TECHNOLOGY COMPETITION IN IMPROVING ENTREPRENEURIAL COMPETITIVENESS - Harahap, Ahmad Fauzi; Harahap, Imam Samtama; Harahap, Henny Azizah; Tambunan , Nurheprina Sari; Sipahutar, Sahlan Al Muqharam (Academic Solution Publisher, 2025)
This research aims to analyze how technology can enhance the competitiveness of entrepreneurs, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector in the digital era. Using the case study method and a qualitative approach, this research examines various relevant literature, documents, and secondary data without conducting direct field observations. The analysis results show that digital technology plays a very important role as the main driver of innovation, improving operational efficiency, and expanding market access. In addition, legal regulations such as consumer protection, intellectual property rights, and data security become factors that support the creation of professional and sustainable businesses. Innovation, business adaptation, and the use of data and analytics have proven to enhance the ability of SMEs to face market changes and build stronger relationships with customers. Collaboration between technology, sustainable innovation, customer focus, and data-driven decision-making is the key to creating competitive entrepreneurship amidst the rapidly changing times.